Interacting environmental stress factors affects targeted metabolomic profiles in stored natural wheat and that inoculated with F. graminearum - García-Cela, Esther; Kiaitsi, Elisavet; Medina, Angel; Sulyok, Michael; Krska, Rudolf; Magan, Naresh (MDPI, 2018)
Changes in environmental stress impact on secondary metabolite (SM) production profiles. Few studies have examined targeted SM production patterns in relation to interacting environmental conditions in stored cereals. The objectives were to examine the effect of water activity (aw; 0.95–0.90) x temperature (10–25 °C) on SM production on naturally contaminated stored wheat and that inoculated with Fusarium graminearum. Samples were analysed using Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) on (a) total number of known SMs, (b) their concentrations and (c) changes under environmental stress. 24 Fusarium metabolites were quantified. Interestingly, statistical differences (ChisSq., p < 0.001) were observed in the number of SMs produced under different sets of interacting environmental conditions. The dominant metabolites in natural stored grain were deoxynivalenol (DON) and nivalenol (NIV) followed by a range of enniatins (A, A1, B, B1), apicidin and DON-3-glucoside at 10 °C. Increasing temperature promoted the biosynthesis of other SMs such as aurofusarin, moniliformin, zearalenone (ZEN) and their derivatives. Natural wheat + F. graminearum inoculation resulted in a significant increase in the number of metabolites produced (ChisSq., p < 0.001). For ZEN and its derivatives, more was produced under cooler storage conditions. Fusarin C was enhanced in contrast to that for the enniatin group. The relative ratios of certain groups of targeted SM changed with environmental stress. Both temperature and aw affected the amounts of metabolites present, especially of DON and ZEN. This study suggests that the dominant SMs produced in stored temperate cereals are the mycotoxins for which legislation exists. However, there are changes in the ratios of key metabolites which could influence the relative contamination with individual compounds. Thus, in the future, under more extreme environmental stresses, different dominant SMs may be formed which could make present legislation out of step with the future contamination which might occur.
Keywords: secondary metabolites; water activity; temperature; environmental stress; mycotoxins; Fusarium graminearum; storage; wheat